Road vehicle following system with adaptive controller gain using model reference adaptive control method lyapunov approaches - Mohamad Sapiee, Mohd Razali; Noordin, Aminurrashid; Basar, Mohd Farriz; Rasin, Zulhani; Talib, Md Hairul Nizam (2010)
In order to maintain stability and satisfy operating constraints, the control system on the following vehicle needs information about the motion of preceding vehicle. A one-vehicle look-ahead control strategy is proposed and will be investigated for this operation. A mathematical model for this control strategy is obtained and simulated. This paper describes the process of designing an adaptive controller gain for a road vehicle following system using two Lyapunov approach. One approaches utilizes the perfect modelling while the other does not. This is done through simulations and comparisons and is further discussed to find the effectiveness of the two Lyapunov approaches.